Pengaruh Kualitas Layanan Produk dan Harga Terhadap Kepuasan Pelanggan Pengguna XL di Kota Banjarmasin (Studi Pada Pengguna Paket Data Internet) - Muhammad Najwan Ridho Allana; Noor Hidayati; Khairussalam Khairussalam (Smart Business Journal, 2021)
The purpose of this research is to find out and examine the effect partially and simultaneously Service Quality (X1) and Price (X2) on Customer Satisfaction (Y) XL users in Banjarmasin city. This study uses a quantitative approach with an associative type. The population in the study were all XL 4G users or consumers in Banjarmasin City. The total sample was 120 people using accidental sampling. The data collection technique was using a questionnaire and the data analysis technique used was Multiple Linear Regression. The research results prove that Service Quality (X1) partially has a significant positive effect on Customer Satisfaction (Y) with the Sig. 0.037 <0.05. And Price (X2) partially has a significant positive effect on Customer Satisfaction (Y) with the value of Sig. 0.000 <0.05. The test results simultaneously show that service quality (X1) and price (X2) have a significant positive effect on customer satisfaction (Y) with the Sig. 0.000 <0.05. Keywords : Service Quality, Price, and Customer Satisfaction